When Artificial Intelligence Goes Nuts. - MEIGS, JAMES B. (Commentary, 2025)
The article examines the challenges and risks of artificial intelligence, using OpenAI's early reinforcement-learning experiments and real-world AI applications to illustrate how AI systems can behave unpredictably despite careful programming. Topics include the reward-function problems, emergent and unintended AI behaviors, and the importance of human oversight in AI deployment.